Assessment of Lightning Current Injection Tests in Replicating the In-flight Current Distribution on Aircraft - Jonnalagadda, Surekha; Kumar, Udaya (Amrit Research Journal, 2024)
Lightning is one of the natural threats to an aircraft. Laboratory tests are usually limited to aircraft component levels and scaled prototypes. For small aircraft, sometimes the whole aircraft could be subjected to the lightning current specified in the relevant standards. Lightning current injection tests are carried out with standard components A to D. This is in anticipation of producing expected levels of fields and current values during a lightning strike. However, generating a current waveform with a rise time and magnitude the same as component A is very difficult in practice. Further, standards specify a return conductor (RC) arrangement for testing. Fields generated due to RC current can affect the current and field distribution. Hence, the emulated current and field in such tests could differ from that in an actual strike. The present work evaluates the current distribution for different lightning current waveforms suggested in standards and that realised in the laboratory. Also, the effect of the return cage on the current/field distribution is studied. The current and voltage distribution on aircraft skin is obtained by employing the impedance network method. A discretised model of Standard Dynamics Model (SDM) aircraft is employed for the present study. It is found that the surface current distribution on aircraft during a laboratory test can differ from that during the actual strike. Owing to the inductance of the aircraft, the rise time of the lightning current realised in the laboratory could be slow compared to that specified in standards; hence, it could also affect the current distribution on aircraft. This work is intended to provide insight into the inherent limitations of laboratory-level testing, which could be helpful for designers.